Resilience as a Psychological Strength in Facing Stress Among Young Soldiers in the TNI AL: A Positive Psychology Perspective Literature Review - Miki Apriani; Ratna Dyah Suryaratri; Gumgum Gumelar; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
The transition phase of young Indonesian Navy (TNI AL) soldiers from education to active duty represents a critical period marked by physical, psychological, and social pressures. Within the framework of positive psychology, resilience is viewed as a psychological strength that enables individuals to endure and thrive amidst such stressors. This study presents a literature review of selected scholarly articles published between 2015 and 2024, examining the relationship between stress, resilience, and supporting psychological factors within military contexts. The main findings highlight the central role of resilience as a psychological safeguard, supported by mediating factors such as hardiness, adaptive coping strategies, and social support. This review also emphasizes that resilience is not merely an innate trait, but a capacity that can be cultivated through training and interventions grounded in positive psychology. The article offers important implications for the development of mental resilience enhancement programs for young soldiers, as well as theoretical contributions to the body of positive psychology literature in military settings.